Decoding Protein Gas‐Phase Stability with Alanine Scanning and Collision‐Induced Unfolding Ion Mobility Mass Spectrometry. Issue 1 (5th January 2021) - Bellamy‐Carter, Jeddidiah; O'Grady, Louisa; Passmore, Munro; Jenner, Matthew; Oldham, Neil J.
Abstract: Invited for this month's cover are the collaborating groups of Professor Neil Oldham at the University of Nottingham and Dr. Matthew Jenner at the University of Warwick, UK. The cover picture shows collision induced unfolding (CIU) of an acyl carrier protein in the gas‐phase as measured by ion mobility spectrometry. The background shows a representation of the alanine scanning mutagenesis used to probe the importance of individual residues in stabilising the compact form of the protein. Read the full text of the article at 10.1002/anse.202000019 . Abstract : "Native mass spectrometry is an exciting and expanding area of research that allows the study of biomolecular structure and interactions with the speed and sensitivity of mass spectrometry. There are differences in the relative importance of the various classes of noncovalent interactions in the solution and gas‐phases. This motivated us to use alanine scanning to assess the ability of specific amino acid residues to stabilise the compact gas‐phase structure of a small protein. Read more about the story behind the cover in the Cover Profile and about the research itself at 10.1002/anse.2020000019 .